Analysis of Question Items and Processing of Islamic Religious Education Learning Evaluation Results - Trias Loudyana Hartati; Muhammad Abdul Kholik; Muhamad Soher; Fadli Rais (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the quality of test items and the processing of evaluation results in Islamic Education (PAI) learning. Using a literature review method, this research examines theoretical frameworks and empirical findings related to item validity, reliability, difficulty index, discrimination power, and distractor effectiveness. The data were analyzed descriptively to identify conceptual patterns and best practices in assessment quality improvement. The findings indicate that systematic item analysis enhances test accuracy, objectivity, and fairness. Furthermore, proper evaluation result processing supports teachers in making data-based pedagogical decisions. It is concluded that item analysis is a strategic component in improving the quality of Islamic Education assessment in contemporary educational settings.